Pembentukan Karakter Religius Siswa Melalui Program Majelis Pagi di SD Islam Terpadu Lentera Hati - Maghfirotul Aliyah; Husni Wakhyudin; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to describe and analyze the formation of students' religious character through the morning assembly program. This study uses a qualitative research method with a descriptive approach. In this study, researchers used several methods to collect data, including: interviews, observations, questionnaires and documentation. The data analysis technique used is triangulation technique. The results of this study indicate that. the formation of students' religious character is done through habituation, understanding, and imitation. Habituation is done through the implementation of the dhuha prayer, reading Asmaul Husna, memorizing/murajaah chapter 30 of the Qur'an, traveling tadarus, celebrating Islamic holidays, and mabit. The understanding process is carried out by integrating character values in learning, Islamic stories, small group studies from teacher, and providing motivation. For example, the teacher gives direct examples to students, during learning during this pandemic the teacher is actively communicating and collaborating with parents to set a good example for children, respecting older and younger people, speaking politely, maintaining friendship. , and help each other.of students.